Pendugaan Produksi Padi Dengan Menggunakan Citra Landsat 8 di Kabupaten Tabanan - FERNANDO JOSUA SINAGA; I WAYAN NUARSA; I KETUT SARDIANA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2020)
Estimation of Rice Production Using Landsat 8 Satellite in Tabanan District Agricultural sector is currently a very important sector considering that everyhuman being needs food to survive and as a source of energy to carry out dailyactivities. Production estimation that are accurate and timely can provide informationfor planners and decision-makers to formulate appropriate policies when conditionsare inadequate or overstocked. The technology that can be used is remote sensing usingthe Landsat 8 satellite. The greenness level parameters of plants (Vegetation Index)obtained through satellite image analysis can be used to estimate rice production. Theresearch area is located in Tabanan Regency. Estimation of rice production is done bythe equation y = 2.0442e1.8787x, where x is the NDVI value from the Landsat 8 imageand y is the result of rice production. The estimation results using Landsat 8 are oneseason production in tons/ha. The accuracy test is done by paired t-test and correlationanalysis. Paired t-test shows that there are no significant differences between riceproduction estimation from BP3K and rice production estimation using Landsat 8.Correlation analysis results show that there is a linear relationship between statisticalresults and estimation results with R2value 0.9682 with the equation y = 1.0099x -0.0794, where y and x are Landsat 8 estimates in tons/ha and BP3K data respectively,with a Standard Error (SE) of 0.1984.